Standardized protocol for laboratory rearing and breeding of the Lymnaeidae snail, Radix natalensis (Krauss, 1848) - Agrippa Dube; Chester Kalinda; Tawanda Manyangadze; Tendai Makoni; Moses John Chimbari (PLoS ONE, 2025)
Freshwater lymnaeid snails are involved in the transmission of fascioliasis in tropical and subtropical Africa, Asia, as well as in temperate regions. This study improved and standardized laboratory rearing and breeding of first-generation (F 1 ) R. natalensis using field-collected F 0 snails. Ninety field-collected R. natalensis adult snails with shell heights of 4–5 mm were divided into three experimental treatment groups: A, B, and C. Each experimental treatment group comprised of ten (10) 2L containers, with each containing 3 snails. Group A, the control, was fed Elodea sp. weed powder and Cyperus papyrus twigs from snail-sampling sites as oviposition material. Group A containers were filled with water from the snail sample sites. Spring-watered snails in experimental group B were fed with dried lettuce, fish flakes, and eggshells. In experimental group C, snails were fed with algal wafers and trout pellets in dechlorinated water. Groups B and C used polystyrene strips for oviposition. Daily snail mortality and egg mass counts were obtained. Experimental group B snails produced 69 egg masses and 500 F 1 offspring with the lowest snail mortality (13%). Group C produced 60 egg masses and 450 F 1 offspring. The mortality rate in this group was 20%. Group A control snails laid 10 eggs and 48 F 1 offspring. Also, mortality (66%) was higher in this group. Mean egg masses differed significantly between groups A and B (Group A: 0.85 ± 0.22 egg masses; Group B: 2.33 ± 0.53, p = 0.034) and A and C (Group A: 0.85 ± 0.22 egg masses; Group C: 2.16 ± 0.48, p = 0.041), but not between groups B and C. Treatment differences explained 11.4% (F 1, 25 = 4.36, p = 0.047) of egg mass variability. The median snail survival in group B was 8.11 days versus 4.57 days in group A. Significant differences in median survival time were observed between experimental groups (Log Rank X² = 9.87, p = 0.007). Group B had the highest fecundity and lowest mortality among the treatment groups. However, the use of spring water increased the costs of mass breeding of snails using this approach. On the other hand, experimental group C produced a comparable number of egg masses. Thus, for mass breeding of R. natalensis , the use of an experimental approach from group C would be recommended as it is cheaper.